The Impact and Mechanism of China's Environmental Protection Tax Policy on Green Technological Innovation in Heavily Polluting Enterprises (2015-2024) - Zhang, Suqin; Kotrba, Vojtěch; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This study analyzes the effect of China’s 2018 Environmental Protection Tax Law on green technological innovation in heavily polluting firms, using panel data of A–share listed companies (2015–2024) and a difference-in-differences approach. ESG performance and R&D investment are identified as key mediators, while media environmental attention serves as a moderator. Robustness checks and heterogeneity analyses across ownership, firm size, regulation, industry technology intensity, and marketization support the findings. Results show the tax significantly promotes green innovation, with stronger effects under positive media attention and in public-sector, large, or technology-intensive firms. The study offers micro-level evidence supporting the Porter Hypothesis and informs policy design to advance China’s green transformation and dual carbon goals.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses